2013
DOI: 10.5194/angeo-31-1485-2013
|View full text |Cite
|
Sign up to set email alerts
|

Electron pitch-angle diffusion: resonant scattering by waves vs. nonadiabatic effects

Abstract: In this paper we investigate the electron pitch-angle diffusion coefficients in the night-side inner magnetosphere around the geostationary orbit (L ~ 7) due to magnetic field deformation. We compare the effects of resonant wave–particle scattering by lower band chorus waves and the adiabaticity violation of electron motion due to the strong curvature of field lines in the vicinity of the equator. For a realistic magnetic field configuration, the nonadiabatic effects are more important than the wave–par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 30 publications
(45 reference statements)
2
32
0
Order By: Relevance
“…However, the more likely situation, where K p < 2, would probably lead to almost no reduction of the magnetic local time‐averaged lifetimes. Another possibility would be an increased pitch angle diffusion of high‐energy (>1 MeV) electrons caused by a strongly reduced magnetic field line curvature in the midnight sector at GEO during disturbed periods [ Artemyev et al , ]. But such effects are expected to occur at GEO only during important disturbances, while the present study focuses instead on moderately disturbed periods during the long recovery phase of storms.…”
Section: Discussionmentioning
confidence: 96%
“…However, the more likely situation, where K p < 2, would probably lead to almost no reduction of the magnetic local time‐averaged lifetimes. Another possibility would be an increased pitch angle diffusion of high‐energy (>1 MeV) electrons caused by a strongly reduced magnetic field line curvature in the midnight sector at GEO during disturbed periods [ Artemyev et al , ]. But such effects are expected to occur at GEO only during important disturbances, while the present study focuses instead on moderately disturbed periods during the long recovery phase of storms.…”
Section: Discussionmentioning
confidence: 96%
“…Figure 3 shows the magnetic field (B x , B y , B z , and B t in the GSM coordinate system) measured by the Electric and Magnetic Field Instrument Suite and Integrated Science (EMFISIS) , the spinaveraged electron fluxes measured by the Magnetic Electron Ion Spectrometer (MagEIS) [Blake et al, 2013], and Relativistic Electron-Proton Telescope (REPT) instruments of the Energetic particle, Composition, and Thermal plasma suite [Spence et al, 2013] on RBSP-A between 15:00 UT on 15 August Figure 3). Birmingham [1984] and Artemyev et al [2013] have shown that nonadiabatic motion in strongly curved magnetic field lines can result in the electron scattering near equatorial plane. Based on the observations of 1.8 MeV electron fluxes from RBSP-A at 18:52 UT on 15 August (j 1 ), 01:20 UT (j 2 ), and 03:46 UT (j 3 ) on 16 August 2013 (as indicated by the three red dots in Figure 3c), the role of substorm electron injections in the recovery and enhancements of electron fluxes at L *~5 .4 was calculated.…”
Section: Themis-a and Geosynchronous Orbit Satellite Observationsmentioning
confidence: 99%
“…Transport of hot magnetotail ions into the inner magnetosphere is critical to the formation of the ring current system [e.g., Daglis et al , ; Gkioulidou et al , , and references therein] and generation of ultralow frequency waves [see Hughes et al , ; Glassmeier et al , ; Dai et al , , and references therein]. Electric currents of hot ions significantly deform the magnetic field configuration in the nightside magnetosphere, influencing the dynamics [ West et al , ; Sergeev et al , ; Artemyev et al , ] and scattering [ Orlova and Shprits , , ; Ni et al , ] of relativistic electrons. The local magnetic field configuration also affects whistler wave generation [e.g., Trakhtengerts , ; Omura et al , ; Katoh and Omura , ; Tao et al , ].…”
Section: Introductionmentioning
confidence: 99%